2015
DOI: 10.7763/ijtef.2015.v6.445
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Impacts of Dolphin Watching as a Tourism Activity: Western Mauritius as Case Study

Abstract: Abstract-Dolphin-watching is now a major tourist attraction in many tropical islands. In the quest of capitalising on this opportunity, some destinations often overlook the impacts and implications of conducting such an activity. In the case of island destinations, it becomes more important to investigate this form of tourism attraction, given that islands face scarcity of resources and their self-sustaining growth are limited. With this as foundation, the present study investigates the impacts of dolphin watc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Previous studies in other countries about CoC have produced similar results, indicating that operators are broadly aware of their existence (e.g. Gaitree and Ian, 2015;Inman et al, 2016;Parsons and Woods-Ballard, 2003).…”
Section: Attitudes and Perceptions On Cbt And Code Of Conductsupporting
confidence: 68%
See 3 more Smart Citations
“…Previous studies in other countries about CoC have produced similar results, indicating that operators are broadly aware of their existence (e.g. Gaitree and Ian, 2015;Inman et al, 2016;Parsons and Woods-Ballard, 2003).…”
Section: Attitudes and Perceptions On Cbt And Code Of Conductsupporting
confidence: 68%
“…It was also shown that if clients' expectations are managed prior to the experience (pre-tour brief), their levels of satisfaction will increase (Filby et al, 2015). A formal training of the boat crew on aspects such as boat and swimmer approach, dolphin behaviour, data collection, and guiding skills has been suggested in many research papers and put into practice successfully by some operators (Buultjens et al, 2016;Filby et al, 2015;Gaitree and Ian, 2015;Nicholls et al, 2013;Parsons, 2012).…”
Section: Attitudes and Perception On Cbt And Code Of Conductmentioning
confidence: 99%
See 2 more Smart Citations
“…Another reality of island tourism is that, very often, foreign-controlled tourism businesses take over local small enterprises, and locals welcome the initiative and thus support tourism as it gives opportunity for international exposure, business growth, and marketing. In other cases, locals choose not to support tourism when they perceive tourism as an industry that trade off their living environment for money (Gowreesunkar et al, 2014). Thus, it is legitimate to suggest that in most cases local entrepreneurs choose to support tourism if they perceive social benefit and business opportunities associated with the tourism development (Das and Sharma, 2009).…”
Section: Support For Tourism Development -The Tourism Entrepreneur Pe...mentioning
confidence: 99%